Proceedings of the EuroSun 2010 Conference 2010
DOI: 10.18086/eurosun.2010.07.02
|View full text |Cite
|
Sign up to set email alerts
|

Condensation Heat Gains on Unglazed Solar Collectors in Heat Pump Systems

Abstract: The performance of ground coupled heat pump systems with borehole heat exchangers can be significantly improved by unglazed solar collectors. In this combination, collector operation temperatures below the ambient air level and hence additional condensation heat gains occur. For an investigated and monitored system in Limburg, Germany, the condensation yield was determined to 3.7% or 19 kWh/(a m²). Thereby, condensation shows a significant dependency on the season. During the summer months, only 0.8% of the to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Hence, in addition to resulting in a higher COP for the heat pump, i.e. up to 4-5 [24,33], the combination of solar collector with DTES also allows for reducing the borehole depth 4.5 to 7.7 m per square meter of solar collector area [34]. However, for a single family house with a single borehole, the economical aspect of recharging should be considered.…”
Section: Duct Thermal Energy Storage (Dtes)mentioning
confidence: 99%
“…Hence, in addition to resulting in a higher COP for the heat pump, i.e. up to 4-5 [24,33], the combination of solar collector with DTES also allows for reducing the borehole depth 4.5 to 7.7 m per square meter of solar collector area [34]. However, for a single family house with a single borehole, the economical aspect of recharging should be considered.…”
Section: Duct Thermal Energy Storage (Dtes)mentioning
confidence: 99%
“…Another promising field of application is the renewable support of heat supply systems for hot water production, space heating or cooling, which has been taken anew into consideration within the last years due to growing market of heat pumps. In this case high-quality metallic absorbers are requested, which can replace parts of the building envelope (roofs or façades) and take over the corresponding functions, both in new buildings and building renovation [11,12].…”
Section: Uncovered Collectorsmentioning
confidence: 99%
“…In Germany, estimated annual condensation heat gains are less than 10% (Pitz-Paal 1988, p.62) whereas first measurements revealed a much smaller fraction of condensation. Measurements on a single family dwelling in Limburg (DE), the condensation yield was determined to be 3.7% of the annual collector yield which corresponds to 19 kWh/(a m²) (Bertram et al 2010). Thereby, condensation shows a significant dependency on the season.…”
Section: Condensation Impact On Systemsmentioning
confidence: 99%
“…A TRNSYS simulation study (Bertram et al 2010) revealed a negligible influence on the seasonal performance factor. Here, the maximum calculated difference in the SPF is calculated to be 0.015 or correspondingly about 0.35% of the electricity consumption.…”
Section: Condensation Impact On Systemsmentioning
confidence: 99%
See 1 more Smart Citation